Development of locomotion strategy for bipedal robot in indoor environment - Md. Akhtaruzzaman (Kulliyyah of Engineering, International Islamic University Ma;aysia, 2012)
A human like sovereign system that is capable to adapt itself with the changing of its environment and continue to reach its goal is considered as a Humanoid Robot. These characteristics differentiate the anthropoid from other kind of robots. In this research, an algorithm is designed and implemented on the BIOLOID humanoid system to perform the locomotion task which is verified with the results from three different experimentations for three different conditions of the robot. The indoor environment is considered with a source and a destination points connected with three different routes with several difficult and complex static obstacles. The map of the environment is predefined for the humanoid system and the main task is to locomote on the routes based on the various commands to reach the goal by avoiding and overcoming the static obstacles. Shifting the Single Support Phase (SSP) to Double Support Phase (DSP) and vice-versa, a natural walking gait is presented through the modeling of Media-Lateral stability of Center of Mass (CoM) and swing leg planning. The practicalities of these gaits are illustrated through the real time experimentation of the bipedal robot. To analyze the behavior of each joint actuator, angular changing patterns are also demonstrated and scrutinized. The performance of the system shows that such a gait is viable for executing motion of an anthropomorphic robot and could be implemented in well designed real size androids to establish a locomotion system.